Evaluation of the Usage of Erythropoietin in Patients with End-Stage Chronic Kidney Disease Dialysis Cycle in Hanoi Nephrology Hospital - Thi Hoa, Do; Thi Tuyet Trinh, Nguyen; Thi Lien Huong, Nguyen; Tung Linh, Phan (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 1DO - 10.25073/2588-1132/vnumps.4202, 2020)
Treatment and control of anemia plays an important role in improving the quality and effectiveness of artificial kidney. The study was conducted on 61 patients who met the selection and were not included in the excluded criteria group. Collecting data from medical records using retrospective, descriptive, vertical follow-up method for 6 months. Data were processed using Microsoft Excel Office 2010 and R. The results showed that patients used both EPO alpha and EPO beta simultaneously. Rate of usage’s EPO beta accounted for 23%, alpha EPO was 77%. Lyophilized form (EPO alpha) is most commonly used. Starting from T3, Hb. averages treat. There were no abnormalities in blood pressure, white blood cell, platelets, and electrolytes. Keywords Hanoi Kidney Hospital, EPO (erythropoietin), Hb, efficacy and safety. References [1] L.A. Szczech, W. Harmon, T.H. Hostetter et al, World Kidney Day 2009: Problem and Challenges in the Emering Epidemic of Kidney Disease, J Am Soc Nephrol 20 (2009) 453-455. https://doi.org/10.1681/ASN.2009010041. [2] D.T. Gilbertson, J. Liu et al, Projecting the Number of Patient with End Stage Renal Disease in the United States to the Year 2015, J Am Soc Nephrol 16 (2005) 3736-3741. https://doi.org/10.1681/ASN.2005010112. [3] A.E. Gaweda, G.R. Aronoff et al, Individualized anemia management reduces hemoglobin variability in hemodialysis patients, J Am Soc Nephrol 25(1) (2014) 159-66. https://doi.org/10.1681/ASN.2013010089. [4] Do Thi Thu Hien, Evaluation of the usage of erythropoietin in the treatment of anemia in patients with chronic renal failure on dialysis at Thai Binh Provincial General Hospital, Master of Pharmacy thesis, Hanoi University of Pharmacy, 2015 (in Vietnamese). [5] Trieu Thi Tuyet Van, Evaluation of the usage of erythropoietin in the treatment of anemia in patients with chronic renal failure on dialysis at the artificial kidney department - Bach Mai Hospital, Master of Pharmacy thesis, Hanoi University of Pharmacy, 2009 (in Vietnamese). [6] Nguyen Thi Uyen, Investigating the effectiveness and safety of Erythropoietin use in dialysis patients at artificial kidney monotherapy Sanit Paul Hospital, Graduation thesis of Pharmacist, Hanoi University of Pharmacy, 2016 (in Vietnamese). [7] Bui Thi Tam, Evaluation the effectiveness of anemia treatment with Erythropoietin in patients with chronic renal failure receiving dialysis at Dien Bien Provincial General Hospital, Graduation thesis of Pharmacist Specialist 2, Hanoi University of Pharmacy, 2011 (in Vietnamese). [8] Drug Administration of Vietnam - Ministry of health, Official dispatch number 4764/QLD-ĐK, 2014 (in Vietnamese). [9] The Vietnam Urology & Nephrology Association, Guidelines for treatment of anemia in chronic kidney disease, The Vietnam Urology & Nephrology Association, 2013 (in Vietnamese). [10] KDIGO, KDIGO 2012 Clinical practice guideline for the evaluation and management of chronic kidney disease, Kidney International Supplement, 2013, pp.1-150. [11] Lam Thanh Vung, Study on the characteristics of anemia and the effectiveness of Erythropoietin β combination with intravenous iron in patients with chronic renal dialysis by dialysis, Thesis Specialized level 2 Medical and Pharmaceutical University, Hue University, 2013.